Effect of Impregnated Mosquito Bed Nets on the Prevalence of Malaria among Pregnant Women in Foumban Subdivision, West Region of Cameroon - Ngouyamsa N. A. Sidiki; Vincent Khan Payne; Yamssi Cedric; Noumedem A. C. Nadia (Journal of Parasitology Research)
Background. Malaria is one of the major public health problems in many tropical developing countries including Cameroon. Impregnated mosquito bed nets are one of the control measures put in place by the WHO and adopted by the Cameroon’s Ministry of Public Health to fight against malaria in pregnancy. This study was a population-based cross-sectional study that investigated the level of adherence, respondent’s knowledge, altitude, and practices toward malaria prevention and control. Methods. To investigate this, a sample size of 410 pregnant women who were inhabitants of Foumban Subdivision was examined. Data on net ownership versus usage, pregnancy status, and socioeconomic background were collected using a questionnaire. Parasitological tests for malaria parasites were carried out using peripheral blood samples obtained from finger pricks of the pregnant women for the preparation of thick blood smear and RDTs. Results. Two hundred and eighteen tested positive (53.4%) with the highest prevalence occurring during the first trimester (79.6%) and in primigravidae (68.8%). Participants believed that mosquito bed nets can protect them against malaria infection. The highest number (81.0%) of the women who had mosquito nets acquired them during antenatal visits. Among those who possessed nets, 42.7% adhered to sleeping under them and few (50%) experienced problems of sweating, discomfort, and heat. Also, the study revealed a high prevalence rate of 63.8% for those who did not use nets during pregnancy as compared to those who owned and used them. Conclusion. The findings indicated that increased access to impregnated mosquito bed nets is required to lower the risk of malaria infection amongst pregnant women. The Cameroon government should improve health education to families within the locality and pursue an integrated approach to fight against mosquitoes during the rainy season.